N6 -Methyladenosine Modification in Chronic Stress Response Due to Social Hierarchy Positioning of Mice - dos Santos Guilherme, Malena; Tsoutsouli, Theodora; Todorov, Hristo; Teifel, Sina; Nguyen, Vu Thu Thuy; Gerber, Susanne; Endres, Kristina (Frontiers in Cell and Developmental Biology, 2021)
Appropriately responding to stressful events is essential for maintaining health and well-being of any organism. Concerning social stress, the response is not always as straightforward as reacting to physical stressors, e.g. extreme heat, and thus has to be balanced subtly. Particularly, regulatory mechanisms contributing to gaining resilience in the face of mild social stress are not fully deciphered yet. We employed an intrinsic social hierarchy stress paradigm in mice of both sexes to identify critical factors for potential coping strategies. While global transcriptomic changes could not be observed in male mice, several genes previously reported to be involved in synaptic plasticity, learning, and anxiety-like behavior were differentially regulated in female mice. Moreover, changes in N6-methyladenosine(m6A)-modification of mRNA occurred associated with corticosterone level in both sexes with e.g. increased global amount in submissive female mice. In accordance with this, METTL14 and WTAP, subunits of the methyltransferase complex, showed elevated levels in submissive female mice. N6-adenosyl-methylation is the most prominent type of mRNA methylation and plays a crucial role in processes such as metabolism, but also response to physical stress. Our findings underpin its essential role by also providing a link to social stress evoked by hierarchy building within same-sex groups. As recently, search for small molecule modifiers for the respective class of RNA modifying enzymes has started, this might even lead to new therapeutic approaches against stress disorders.